2018
DOI: 10.1055/s-0038-1669952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Knee Kinematics and Kinetics during Stair Ascent in Single-Radius and Multiradius Total Knee Arthroplasty

Abstract: Traditionally total knee arthroplasty (TKA) design has been based on theories of the movement of the healthy knee joint. Currently, there are two competing theories on the flexion/extension axis of rotation of the knee with disparate radii of rotation, and thus differing movement patterns. The purpose of our study was to compare stair ascent kinematics and kinetics of single-radius (SR) and multiradius (MR) TKA subjects. We hypothesized that the knee kinematics and kinetics of SR TKA patients would more closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…16 There are also other studies which report better knee kinematics in SR than MR TKA. 10,11,21 However, MP TKA and more recently GR TKA have been shown to more closely mimic normal knee kinematics and produce a medial pivot pattern. 13,19,22,23…”
Section: Mid-flexion Instability and Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 There are also other studies which report better knee kinematics in SR than MR TKA. 10,11,21 However, MP TKA and more recently GR TKA have been shown to more closely mimic normal knee kinematics and produce a medial pivot pattern. 13,19,22,23…”
Section: Mid-flexion Instability and Kinematicsmentioning
confidence: 99%
“…24 There are biomechanical and clinical studies which have shown improved quadricep strength and function in SR TKA as compared to MR TKA. 11,21,25,26 However, a recent randomized controlled trial by Kim et al comparing SR TKA (Triathlon®, Stryker, Mahwah, New Jersey) and MR TKR (PFC Sigma®, Depuy Synthes, Warsaw, Indiana), showed no difference in quadricep strength and recovery at one year postoperatively. 27…”
Section: Quadriceps Functionmentioning
confidence: 99%
“…The three ADLs had similar reductions in knee extensor moment and knee power for MR subjects in comparison to age-matched controls. During stair ascent SR subjects also had reduced knee extensor moment and knee power compared with controls, 18 while SR were statistically indistinguishable from controls for level walking and stair descent. 17 Along with the reduction seen in ADL, a reduction in the internal extension moment was found during flexion/extension leg press exercises and in cadaveric knees.…”
Section: Discussionmentioning
confidence: 84%
“…Previous research in our laboratory found that the SR design TKA more closely replicates normal walking and stair ascent kinematics and kinetics than the MR design 1 year after surgery. 17,18 Specifically, knees implanted with MR TKAs had decreased knee flexion, internal extension moment, and power absorption than age-matched controls during level walking. In contrast, no significant differences were identified between 1-year postoperative SR TKAs and age-matched controls in any biomechanical parameters.…”
mentioning
confidence: 99%